Linguistic Feasibility Analysis of Grade V Arabic Textbook by Nur Hidayah Press BSKAP Perspective - Jovial Elitahari; Naifah Naifah (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2026)
The linguistic quality of Arabic textbooks is very important for optimal learning at the Madrasah Ibtidaiyah level. Linguistic errors, inconsistent terminology, poor readability, and ambiguous instructions can hinder student comprehension and increase cognitive load. This study aims to evaluate the linguistic suitability of fifth-grade Arabic textbooks published by Nur Hidayah Press in accordance with the guidelines set by the Education Curriculum and Assessment Standards Agency (BSKAP). This research uses a qualitative descriptive methodology through library research. Data were collected through documentation methods by analyzing the linguistic elements of the textbooks, including grammatical accuracy, terminology consistency, sentence clarity, and linguistic simplicity, using twelve linguistic feasibility metrics provided by BSKAP. The results showed that the textbook received a total score of 35 out of 48 (72,92%), categorized as acceptable. Although it generally complied with language standards, there were several shortcomings in terminology consistency, sentence complexity, and instruction clarity. Specific language changes are needed to improve readability, consistency, and instruction clarity for better learning outcomes.